Claim Paying and Reinsurance on Company's Financial Health - Markonah, Markonah; Silalahi, Sriani; Selliamanik, Irma (ADPEBI Publisher, 2023)
Purpose – This research was conducted with the aim of analyzing the effect of claim payments and reinsurance on the company's financial health (Solvability) Asuransi Prudential Indonesia.. Methodology/approach – This research method uses descriptive, associative, and causal methods with a quantitative approach. The population used is Prudential Indonesia's 2006-2021 Annual Financial Report with a total of 16 data. The sampling technique is saturated sampling, so that the sample is 16 data. Data collection techniques with library research and documentation and processed using IBM SPSS. Findings – The data analysis technique used is multiple linear regression with the equation Y = 3.668 + 0.0000006263(X1) + 0.0000001706(X2). The research results show: a) Payment of claims has a significant positive effect on the company's financial health (solvency) Asuransi Prudential Indonesia b) Reinsurance has no effect on the company's financial soundness (solvency) Asuransi Prudential Indonesia c) multiple linear analysis results. d) The R square value of the coefficient of determination which is the effect of claim payments and reinsurance on the company's financial health (solvency) Asuransi Prudential Indonesia is 49.20%. Novelty/value – The higher the payment of claims reflects the higher operational activities so that the financial health is high, so that operational activities need to be improved. Keywords: Claim Payment, Reinsurance, Company's Financial Health (Solvability).